Evaluation of radiographic quality of root canal therapy performed by dental students at Yazd dental school during 2010-2012 - Fateme Mokhtari; Mohammad Hossein Yosefi; Ali Gharaati Jahromi (Tehran University of Medical Sciences, 2014)
Background and Aims: Root canal therapy is one of the most important parts of a general dentist's profession. The aim of this study was to evaluate the radiographic quality of root canal therapy performed by under graduated students at Yazd dental school.   Materials and Methods: Records of patients, who were referred to the endodontic department during 2010-2012 and treated by undergraduated students, were divided into three groups by the numbers of canals and 80 specimens from each group were randomly evaluated. For the assessment, the quality of accomplished treatments, the indices: length, taper, and density of obturation were used and the errors during root treatment were recorded. Data were analyzed using Fisher's exact test and Chi-square.   Results: According to the results, 155 (64.6%) records had appropriate filling length, whereas 55 (22.9%) were underfilled and 30 (12.5%) were overfilled. The acquired difference was statistically significant among three groups. (P<0.001). 187 (77.9%) records had adequate taper and 157 (65.4%) records had adequate density. The difference in the evaluating of taper (P=0.976) and density (P=0.879) was not significant. Totally, 39.2% of specimens had all the properties of an appropriate root canal treatment.   Conclusion: The results of the present study can be used to identify weaknesses in the treatment of different educational groups and help them to achieve a proper planning to improve the quality of endodontic treatments.